1991
DOI: 10.1007/bf00197740
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal periodicity of chalcone-synthase activity during the development of oat primary leaves

Abstract: Chalcone-synthase (CHS) activity was followed during the development of primary leaves of oat (Avena sativa L.) seedlings grown under different illumination conditions. Continuous darkness and continuous light resulted in similar time courses of enzyme activity. The maximum of CHS activity in etiolated leaves was delayed by 1 d and reached about half the level of that of light-grown leaves. In seedlings grown under defined light-dark cycles a diurnal rhythm of CHS activity and its protein level was observed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The phase of the circadian rhythm of CHS was earlier than CAB, with a peak occurring in the late subjective night . Chalcone synthase enzyme activity and mRNA abundance have previously been reported to exhibit diurnal and circadian regulation (Peter et al, 1991; Deikman and Hammer, 1995; Harmer et al, . Luminescence data were analyzed from whole seedlings, without separate analysis of roots and aerial tissues.…”
Section: Regulation Of Chsmentioning
confidence: 99%
“…The phase of the circadian rhythm of CHS was earlier than CAB, with a peak occurring in the late subjective night . Chalcone synthase enzyme activity and mRNA abundance have previously been reported to exhibit diurnal and circadian regulation (Peter et al, 1991; Deikman and Hammer, 1995; Harmer et al, . Luminescence data were analyzed from whole seedlings, without separate analysis of roots and aerial tissues.…”
Section: Regulation Of Chsmentioning
confidence: 99%
“…Further investigations demonstrated that not only transcript levels of photosynthetic genes express diurnal m R N A patterns, but also genes encoding enzymes such as nitrate reductase (nr [11,15]), catalase 3 (cat [46]), phosphoenolpyruvate carboxylase (pepC [57]), chalcone synthase (chs [38]), nitrite reductase (nir [4]), glutamine synthetase (gs [5]), RuBPase activase (rca [29,44]), A and B chaperonin subunits (cpn [44]), two heat-inducible proteins [36] and a biotinbinding protein [16]. Free-running oscillations under constant conditions with a period length of ca.…”
Section: Steady-state Mrna Oscillationsmentioning
confidence: 99%
“…Twenty primary leaves, from different developmental stages or tissue preparations from 20 to 30 defined leaf segments and intact segments (as control) were frozen in liquid nitrogen and ground with a mortar and pestle. Chalcone synthase was immediately extracted as previously described (Peter et al 1991). For epidermal layers the extraction buffer was supplemented with 3 mg bovine serum albumin (BSA, Serva, Heidelberg, FRG) per ml or, in some cases, with 5 mM phenylmethylsulfonyl fluoride (PMSF; Serva), a protease inhibitor, both optimized conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Chalcone synthase was assayed in the presence of 0.5% BSA according to Peter et al (1991). With all leaf or tissue preparations the only reaction product was naringenin, as checked in four different solvents by TLC (Peters 1987;Peters et al 1988).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation